IMPACT OF PANDEMIC COVID-19 ON ENVIRONMENTAL AND AGRICULTURE IN THE PROVINCE OF GORONTALO - Iswan Dunggio; Sofyan Abdullah; Risma Neswati (Jurnal Ecosolum, 2021)
Corona virus disease Covid-19 is a deadly virus and was first discovered in Wuhan, China.This virus has spread throughout the world and has an impact on the environment and Agriculture.The impact on the environment is an increase in waste congeries, a decrease in energy consumption, a decrease in air pollution, while the impact of Covid-19 on the Indonesian economy includes negative economic growth, an increase in the number of poor people and an increase in unemployment. This study aims to analyze the impact of Covid-19 on the environment and agriculture in Gorontalo Province.This study uses a qualitative approach where data is collected from interviews and literature searches from official sources.The results showed that the impact of Covid-19 on environmental conditions in Gorontalo Province, among others, was an increase in waste production by 9.17% during Covid-19 in 2020, and an increase in the use of medical waste for Covid-19 by 33.3% in the fourth quarter of 2020.The use of electrical energy has increased by 6.7% during the Covid-19 pandemic in 2020. As for impact on agriculture contribution of the agricultural sector to GDP was relatively stable, rice production increase 4.1%, but fish production fell by 0.18% and coconut fell 0.11%. This condition can raise farmers term of trade during the 3rd and 4th quarters in 2020